1991
DOI: 10.1111/j.1151-2916.1991.tb06829.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Additions to Molybdenum Disilicide: Improved High‐Temperature Mechanical Properties

Abstract: C addition (2 wt%) to MoSi2 acted as a deoxidant, removing the otherwise ubiquitous siliceous grain boundary phase in hot-pressed samples, and causing formation of SIC and Moj5Si3Cj, (a variable-composition Nowotny phase). Both hardness and fracture toughness of the C-containing alloy were higher than those of the C-free (and oxygen-rich) material; more significantly, the fracture toughness of the MoSil + 2% C alloy increased from 5.5 MPa.m"' at 800°C to -11.5 MPa m"' at 1400°C. [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(44 citation statements)
references
References 2 publications
2
40
2
Order By: Relevance
“…In addition to alloying studies, extensive composite studies have been carried out. Addition of C is seen to improve the oxidation resistance [21]. This is reported to be due to the removal of the siliceous grain boundary.…”
Section: Introductionmentioning
confidence: 95%
“…In addition to alloying studies, extensive composite studies have been carried out. Addition of C is seen to improve the oxidation resistance [21]. This is reported to be due to the removal of the siliceous grain boundary.…”
Section: Introductionmentioning
confidence: 95%
“…In recent years, applications have been proposed or are being attempted in hot-end components of aerospace gas turbines, diesel engine glow plugs, and molten-metal lances. [1] Having being projected as a material for high-temperature structural applications, the thrust of research on MoSi 2 has been on improving the high-temperature mechanical properties [2][3][4][5][6][7][8][9][10][11][12] and establishing a comprehensive understanding of deformation mechanisms. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Single-crystal MoSi 2 has been found to plastically deform even at room temperature [13] in relatively "soft" orientations away from [001], such as [110], [201], or [0 15 1], while polycrystalline MoSi 2 cannot deform without cracking until 1000 °C, as only four independent slip systems have been found to be active at or below 1000 °C.…”
Section: Introductionmentioning
confidence: 99%
“…It may then be possible that by reinforcing with both TiB 2 and SiC, minimization (if not elimination) of pesting at intermediate temperatures and retention of high-temperature strength and creep resistance can be achieved simultaneously. Previous work by the authors has shown that double reinforcement of TiB 2 and SiC increased the room-temperature hardness more than single reinforcement of either TiB 2 or SiC. Dry-sliding wear experiments also showed that the wear rate in the mild-wear region is lower in double reinforcement composites of MoSi 2 .…”
Section: Introductionmentioning
confidence: 53%
“…Furthermore, the appearance of grain-boundary cavities can also be seen, which is found to increase with increasing temperature. Maloy et al 2 reported an intergranular type of fracture at all temperatures for the monolithic MoSi 2 due to the presence of a siliceous intergranular phase. But, in the present study the transition to intergranular is found to occur only above 1300°C.…”
Section: (2) Fractographymentioning
confidence: 99%
See 1 more Smart Citation